Aspects of the release of superoxide by leukocytes, and a means by which this is switched off. - Karnovsky, M L (1994)
Although great progress has been made in understanding the respiratory burst of leukocytes that produce superoxide (O2-), it is possible that a component or components, might have been overlooked. Furthermore, O2- production and its sequels, though cardinal in bactericidal action, might ultimately be damaging to the host's own cells. It is important, therefore, that a biologic mechanism exist to turn off O2- production by stimulated leukocytes. This article offers evidence that methoxatin (PQQ), a redox-cycling orthoquinone, might be involved in O2- production by leukocytes. This is based on the fact that inhibitors of O2- production, such as diphenylene iodonium (DPI) and 4,5-dimethylphenylene diamine (DIMPDA), were shown to sequester PQQ in leukocytes, i.e., to form adducts with that substance. Addition of PQQ to cells blocked with the inhibitors partially restored O2- release. With respect to turning off cellular O2- release, a factor was observed to be released to the medium by old macrophages (14 days old, but not by those less than 7 days old). Such conditioned medium, when added to stimulated neutrophils or macrophages, blocked O2- release. This factor was sensitive to proteases, exhibited molecular sizes of 3 and 11 kDa, and its action was independent of the nature of the stimulus applied to the leukocytes. It was partially purified by column (sizing) chromatography and HPLC. It seems to be a general modulator of the release of reactive oxygen species by phagocytes and is irrespective of phagocytic cellular type, or species from which the cells were derived.